Critical pedagogy and gender norms: insights from Moroccan educational settings - Bendraou, Rachid; Sakale, Sana (Society Register, 2024)
This study investigates the use of critical pedagogy in Moroccan educational settings to challenge persistent gender norms and power dynamics. The thematic analysis of in-depth interviews with educators indicates critical pedagogy's impact on gender role perceptions and practices. The findings show how critical pedagogy encourages critical consciousness and challenges old conventions, promoting gender equity in the classrooms. Teachers’ viewpoints illustrate both the problems and accomplishments of implementing critical pedagogy, emphasizing its ability to foster inclusive learning environments. This study provides insight into critical pedagogy’s transformative impact on instructors’ practices and students’ involvement with gender dynamics in Morocco. By explaining these educational practices, the study highlights critical pedagogy as a catalyst for achieving social justice in Moroccan schools, emphasizing the importance of pedagogical techniques that support equitable learning and question cultural norms.